Analisis Efektivitas dan Kontribusi Pajak Daerah terhadap Pendapatan Asli Daerah Kabupaten Bondowoso - Asmandani, Venantya; Wicaksono, Galih (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
The central government gives authority to local governments to manage and regulate financial policies and management. Regional Autonomy has been implemented in Indonesia since 2001. The Covid-19 pandemic has caused problems for the economic sector in the world, especially in Indonesia. Thus affecting local tax revenues and local revenue receipts. Local governments must look at how effective local taxes are and how much they contribute to local revenue. The Bondowoso government has implemented an extensification and intensification strategy to be able to increase regional tax revenues and local revenue during the pandemic in 2020 and 2021. This study uses an analysis of effectiveness and contribution in Bondowoso in 2020 and 2021. The results of this study are that local taxes have the level of effectiveness for Bondowoso District Original Revenue which is very high in 2020 reaches 104.88% while for 2021 it has a fairly effective level of effectiveness, namely only reaching 84.50%. The contribution of local taxes to local revenue is not significant because it has a small number of PAD contributions, namely 13.73% and 15.70%.